PERAN PUSTAKAWAN DALAM MENINGKATKAN MINAT DAN KEBIASAAN MEMBACA SISWA DI SDN GUNUNG BATU 2 KOTA - Fitri Anjaswuri; Sonia Deya (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
THE ROLE OF LIBRARIANS IN INCREASING STUDENTS’ READING INTEREST IN SDN GUNUNG BATU 2, BOGOR CITYThe purpose of this study was to determine the Role of Librarians in Increasing Student Reading Interest and Habits at SDN Gunung Batu 2, Bogor City. This research is a qualitative research with a descriptive approach. The subjects of this study were students and school librarians at SDN Gunung Batu 2, Bogor City. This research was conducted in the odd semester of 2019/2020. The data collection techniques used were observation, documentation, and interviews. Data collection techniques using the Miles and Huberman method, namely data reduction, data display, and drawing conclusions are carried out continuously until it is complete so that the data is saturated. Test the validity of the data using triangulation of sources and techniques as well as conducting a member check. And the research results show some findings, namely the background of the role of librarians in increasing students 'reading interest as a form of librarian's success in increasing students' reading interest and habits at SDN Gunung Batu 2, Bogor City. Furthermore, based on the results of observations, interviews, and documentation carried out in the field to related parties who know the problems of this thesis. Librarians provide a mandatory library system for all scheduled classes, hold reading corners, provide good service, hold the latest collections in the library, cooperate with regional libraries, always attend seminars or workshops, always include students in storytelling competitions, read poetry which is related to increasing students' reading interest and habits. In increasing students 'reading interest and habits, librarians certainly have a positive impact on students' reading interests and habits in accordance with the expectations of the librarian's own role. Because the role of the librarian has shown good development for students to be more like, happy, and enthusiastic about visiting the library so that the interest and reading habits of students at SDN Gunung Batu 2 Kota Bogor have increased every year according to the existing percentage.